A COMPARATIVE STUDY OF FIANCIAL REPORTING AS PER INDIAN GAAP WITH IND AS: WITH SPECIAL REFERENCE TO RELIANCE INDUSTRIES - Rajpara, Yashasvi; Raval, Kirtan P. (International Journal of Psychosocial Rehabilitation, 2020)
In this era of rapid business growth through connecting with international market place companies are always ready for entering in international business ventures through investing in the another country or operating in another countries by opening business units. For entering in world market companies are required to be uniform in all the aspect of financial reporting so, that they can easily understand the financials of the business organization with which they are entering in the international business. For which international accounting standards board has given one new though of uniform accounting standards in whole world by putting International Financial Reporting standards. Laws of some countries were not allowing to accept these standards directly so, they have done convergence with the IFRS. India is one of those countries which gone for convergence with IFRS and Introduced Converged Indian Accounting Standards. Here, Researcher has made attempt of identifying the key area of impact in financial reporting by comparing the Financials of Reliance Industries as per IGAAP with Ind AS.